Literature Review: Analysisi of Learning Models to Improve Students; Science Process Skills - Mardiah, Anisa Ainul; Sukarno, Sukarno; Supianto, Supianto (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
The aim of the research is to determine the effectiveness of the student center-based learning model for improving science process skills in elementary schools. This research uses a literature review research design with a descriptive qualitative approach. The data in this research is secondary data. Data collection techniques use literature studies related to national journals and international journals that match the research focus. This research analyzes search results originating from the Erics, DOAJ, and Google Scholar databases. Based on the results of research conducted on 21 articles, both national and international, it can be stated that the three learning models can improve students' science process skills. So it can be concluded that the predict observe explain, Project Based Learning, and inquiry models are able to improve students' science process skills.